Synergistic antifungal activity of minocycline as an effective augmenting agent of fluconazole against drug-resistant Candida tropicalis - Yun-Zhu Zhu; Xiang Li; Qing-Yue Zhang; Ning Yang; Ping Tian; Ding Zhang; Yi Yang; Liang Yu; Yan-Yan Liu; Ying Ye; Ya-Sheng Li; Jia-Bin Li (Microbiology Spectrum)
ABSTRACT Invasive candidiasis has emerged as a significant healthcare challenge, with a rising incidence rate attributed to the widespread use of organ transplantation, chemotherapy, immunosuppressants, and broad-spectrum antibiotics. The increasing prevalence of drug-resistant strains, particularly among Candida tropicalis, has necessitated the exploration of novel therapeutic strategies. Our study investigated the synergistic effects of minocycline (MIN) combined with fluconazole (FLC) against FLC-resistant C. tropicalis, both in vitro and in vivo. The in vitro synergistic activity of MIN and FLC was evaluated using checkerboard titration and time-kill assays. The Galleria mellonella larvae and mouse model were employed to assess in vivo efficacy, with histopathological examination and fungal burden quantification. Whole-genome and RNA sequencing elucidated the synergistic mechanisms observed. The FLC/MIN combination significantly lowered the minimum inhibitory concentration (MIC) and improved fungicidal activity, as evidenced by enhanced survival rates and reduced fungal burden in G. mellonella larvae and mouse models. Histopathological analysis confirmed less tissue damage and fungal load with combination therapy. RNA sequencing analysis suggested that the impact of MIN on amino acid metabolism contributes to the synergistic effects. This approach holds promise for treating FLC-resistant C. tropicalis by increasing antifungal efficacy and reducing drug resistance risks, warranting further clinical exploration.IMPORTANCEThis study highlights the potential of minocycline and fluconazole combination therapy in combating drug-resistant Candida tropicalis. It shows promising in vitro and in vivo synergistic effects, reducing MIC and enhancing fungicidal activity. Further clinical trials are needed to validate its efficacy in treating FLC-resistant C. tropicalis infections.